Initial Design of Earthquake Early Warning System With Smartphone Display - Audia, Washilla; Yulkifli, Yulkifli; Yohandri, Yohandri (The Physical Society of Indonesia, 2025)
This research presents the preliminary design of an automatic vibration detection system that can be used as an earthquake early warning system using the Internet of Things and a smartphone display, and to investigate the relationship between vibration acceleration and vibration intensity and magnitude. Earthquake early warning is an important tool to reduce the danger of earthquakes and is a form of earthquake mitigation. This system is designed using MPU6050, ESP8266, Arduino IDE, Buzzer, LCD, and Smartphone sensors. The relationship between variations in vibration intensity and magnitude with vibration acceleration is directly proportional. This system has 96% accuracy and the accuracy of vibration acceleration read on the system is 92%. This system can be a simple earthquake early warning solution in earthquake-prone areas to minimize the risk of earthquake natural disasters and can be used as a basis for developing earthquake disaster mitigation systems.